A shelf-life study for the evaluation of a new biopackaging to preserve the quality of organic chicken meat. (1st March 2022) - Alessandroni, Laura; Caprioli, Giovanni; Faiella, Federico; Fiorini, Dennis; Galli, Renzo; Huang, Xiaohui; Marinelli, Giacomo; Nzekoue, Franks; Ricciutelli, Massimo; Scortichini, Serena; Silvi, Stefania; Tao, Jing; et al.
Highlights: Organic chicken meat in biodegradable packaging. Renewable and compostable biopackaging to preserve chicken meat. Chicken meat shelf-life study through chemical, microbiological and sensorial parameters. New biopackaging can preserve organic chicken meat similarly to plastic material. Abstract: Widespread use of traditional packaging constitutes a serious ecological problem leading to a shift to biodegradable and compostable materials. The aim of this work is to study the ability of a new biopackaging (BP), based on biodegradable and compostable material, to preserve the quality of organic chicken meat for 14 days in comparison with a polyethylene terephthalate (PET) material. Results showed that the indices of Biogenic Amines (BAs) and the 18 monitored Volatile Organic Compounds (VOCs) have a similar trend in both packaged meats. For example, the total BAs concentration in meat increased from 390 to 961 mg Kg −1 in BP and from 393 to 800 mg Kg −1 in PET, as well as the microbiological counts. The new biopackaging (BP) showed similar properties of non-biodegradable material (PET) to preserve the shelf life of organic chicken meat and it could be used instead of plastic materials to promote a circular economy.